Development of aerobic fitness during childhood and adolescence - Armstrong, N.; Welsman, J. R. (Pediatric Exercise Science, 2000)
Over 60 years ago, Robinson published the first investigation of boys' aerobic fitness; almost 50 years ago, Astrand conducted his pioneering studies of both sexes. Twenty four percent of the papers published during the first 10 years of Pediatric Exercise Science (1989-98) involved the determination of peak VO2. Yet, the interpretation of aerobic fitness during childhood and adolescence is still shrouded with controversy. In this paper we review peak VO2 in relation to age, growth, maturation, and sex. We describe the increase in peak VO2 with age, challenge the traditional interpretation of peak VO2 during growth, demonstrate the independent contribution of maturation to peak VO2, and address the progressive divergence of boys' and girls' peak VO2 during childhood and adolescence.